O Exercício Físico como Coadjuvante Terapêutico no Processo de Envelhecimento - Gonçalo Manuel Lencastre Cardia Lima Carneiro (2017)
Nowadays, the aging Portugal´s population, as well as all over the world, is growing as a direct result of both, the increased average life expectancy and the reduction of birth rates to historical lows. According to the statistics (INE, 2016b), in 1985 Portugal was one of the youngest countries in Europe (26% of young people) and moderately aged (11% of elderly). Previsions for 2060 indicate that the aging rate will increase from 131 to 307 elderly people for every 100 young people considered (INE, 2014). The rating disclaiming the potential sustainability indicates a decrease from 340 to 149 active age people for every 100 elderly individuals considered. In 2050, it is estimated that Portugal will be the fourth most aging country in the world, right behind Japan, South Korea and Spain (UN, 2015b). Physical exercise has proven to be a free-prescription path, capable of operating wonders in the human body. Therefore, it is necessary to implement it to deal with physical and functional decay due to the aging process. The main goal of this internship was to promote physical exercise programs in four courses of elderly people. In the beginning and in the end of the year, several tests regarding physical and functional ability were made on each elder, following the Senior Fitness Test. The results were compared according to statistical inference, using the T test, for values within the average, and the Wilcoxon Test, for two non-parametrical samples on values considered unusual. The value achieved was 0,05 (p <0,05). The end results show statistically relevant changes between the initial and final evaluations for most analyzed variables. Such facts suggest an overall improvement on the physical ability of the elder, ensuring also the efficiency of the training protocols applied. The quest is clear, it is one of turning aging into an active and healthy process.